Arbutus unedo L. leaves as source of phytochemicals with bioactive properties - Malheiro, Ricardo (2014)
In recent years the strawberry tree (Arbutus unedo L.) is being gradually replaced by other species with higher economic value. With the ultimate goal of selecting superior genotypes, the present work was initiated to study the antioxidant and antimicrobial activities, and total phenolic content in 19 different genotypes of A. unedo leaves from the Trás-os-Montes region of Portugal. The genotype Braganc¸ a 1 contains higher total phenolic content (215.0 mg GAE/gextract) whereas the Vila Boa 4 genotype shows lower total phenolic content (148.0 mg GAE/gextract). In both methods tested to evaluate the antioxidant activity, Vila Verde and Donai displayed the highest antioxidant capacity (EC50 values of 0.088 and 0.090 mg/mL, respectively, for DPPH; EC50 values of 0.233 and 0.245 mg/mL, respectively, for reducing power assay) while Vila Boa 2 reported the lowest antioxidant potential (EC50 values of 0.142 and 0.378 mg/mL, respectively, in DPPH and reducing power methods). Linear negative correlations were established between the total phenol contents and the EC50 values for both of the antioxidant activity methods tested. Preliminary assays for antimicrobial potential showed that extracts from A. unedo leaves display antibacterial activity, with MIC values of 1 and 5 mg/mL for some Grampositive and Gram-negative bacteria, respectively. Taken together, the results suggest that A. unedo leaves are a potential source of natural compounds with valuable bioactive properties that could be explored by the pharmaceutical, chemical and food industries.